A Layout for the Carbon Capture with Aqueous Ammonia without Salt Precipitation. (January 2016) - Bonalumi, Davide; Valenti, Gianluca; Lillia, Stefano; Fosbøl, Philip L.; Thomsen, Kaj
Abstract: Post-combustion carbon capture technologies seem to be necessary to realize the CO2 mitigation policies internationally shared for the next future, despite none of them appears to be ready for full-scale applications. This work considers the aqueous ammonia-based process for a coal-fired Ultra Super Critical power plant. Two layouts are simulated with Aspen Plus employing the recently recalibrated Extended UNIQUAC thermodynamic model. The first one operates at chilling conditions, which yield to salt precipitation, and is taken as reference because already analyzed in previous studies. The second layout operates at cooled conditions, which does not yield any salt precipitation. The Chilled layout reveals low specific heat duty and SPECCA equal to 2.2 and 2.86 MJ/kgCO2, respectively. In contrast, the Cooled layout presents a higher specific heat duty of almost 3 MJ/kgCO2 but, importantly, a lower SPECCA of 2.58 MJ/kgCO2 . The latter layout is a better choice also from the perspective of the plant operation since it does not present the salt precipitation.